Safety and Efficacy of Citicoline among Acute Ischemic Stroke Bangladeshi Patients: A Randomized Control Trial (Journal of National Institute of Neurosciences Bangladesh, 2023)
Background: Ischemic stroke is the most common type of all stroke events. About 2.7 million people die each year from ischemic stroke. Facilities for reperfusion therapy in hyper-acute state is not widely available in our country. Use of neuro-protective agents like citicoline may be considered as a reasonable adjunct with antiplatelet agents.Objective: The objective of this study was to evaluate the safety and efficacy of citicoline in treatment of acute ischemic stroke as a neuro-protective agent.Methodology: This was a randomized controlled trial which was conducted in Neurology Unit of National Institute of Neurosciences & Hospital, Dhaka, Bangladesh from January 2017 to December 2017. Acute ischemic stroke patients presented with National Institute of Health Stroke Scale (NIHSS) ≥ 5 were recruited for this study. The study population were divided into 2 groups designated as study and control groups. Control group received standard treatment of acute ischemic stroke whereas study participants were treated with standard stroke medications along with citicoline. Outcome and adverse events were recorded at one week and at twelve weeks of treatment onset. The primary end points of outcome were assessed using NIHSS and mRS at twelve weeks. NIHSS ≤1 and/or mRS ≤2 were considered as good functional outcome.Results: A total number of 109 acute ischemic stroke patients were recruited for this study of which 53 cases in the study group and 56 cases in the control group. More number of patients achieved good functional outcome (mRS ≤2) in citicoline group in comparison to control group, 62.96% and 37.03% in study and control group respectively (p=0.362), though this difference was not statistically significant. There were no significant changes of biochemical parameters, major and minor adverse events between two groups at 1 week and 12 weeks follow up. A significant number of patients died in control group in comparison of study group, 45.45% vs. 23.8% (p=0.0483) within 12-week period.Conclusion: In this study, functional outcome is found better in citicoline group. Survival benefit is observed with citicoline group in comparison to control which is statistically significant.Journal of National Institute of Neurosciences Bangladesh, January 2023;9(1):3-10